The Role of Na:K:2Cl Cotransporter 1 (NKCC1/SLC12A2) in Dental Epithelium during Enamel Formation in Mice - Jalali, Rozita; Lodder, Johannes C.; Zandieh-Doulabi, Behrouz; Micha, Dimitra; Melvin, James E.; Catalan, Marcelo A.; Mansvelder, Huibert D.; DenBesten, Pamela; Bronckers, Antonius (Frontiers in Physiology, 2017)
Na+:K+:2Cl- cotransporters (NKCCs) belong to the SLC12A family of cation-coupled Cl- transporters. We investigated whether enamel- producing mouse ameloblasts express NKCCs. Transcripts for Nkcc1 were identified in the mouse dental epithelium by RT-qPCR and NKCC1 protein was immunolocalized in outer enamel epithelium and in the papillary layer but not the ameloblast layer. In incisors of Nkcc1-null mice late maturation ameloblasts were disorganized, shorter and the mineral density of the enamel was reduced by 10% compared to wild-type controls. Protein levels of gap junction protein connexin 43, Na+-dependent bicarbonate cotransporter e1 (NBCe1), and the Cl–dependent bicarbonate exchangers SLC26A3 and SLC26A6 were upregulated in Nkcc1-null enamel organs but the level of NCKX4/SLC24A4,the major K+, Na+ dependent Ca2+ transporter in maturation ameloblasts, was downregulated. Whole-cell voltage clamp studies on rat ameloblast-like HAT-7 cells indicated that bumetanide increased ion-channel activity conducting outward currents. Bumetanide also reduced cell volume of HAT-7 cells. We concluded that non-ameloblast dental epithelium expresses NKCC1 to maintain cell volume in enamel organ. NKCC1 could also provide ameloblasts with Na+, K+ and Cl- ions required for the uptake of mineral and bicarbonate ions. In the absence of functional Nkcc1, other ion channels and transporters can compensate for its absence in the dental epithelium. The increased amount of Cx43 in enamel organ cells in Nkcc1-null mice suggests that these cells display a higher number of gap junctions to increase intercellular communication.